3-D Seismic Identification and Characterization of Ancient Channel Morphology - 蒲仁海 朱李 钟红利 (Journal of earth science (Wuhan, China), 2009)
It is easy to identify ancient fluvial morphologic types by the outcrop,log and core data.However,the horizontal distribution and geometry of the channels can only be identified and predicted by relying on the 3-D seismic data.The 3-D seismic horizon slices,especially,can play an important role in the sandstone prediction of meandering rivers,distributary channels and low-sinuosity channels.Every microfacies unit,including main channels,such as sinuous or branching channels,levee,crevasse channels,ligule crevasse splay and floodplain etc.can be identified.Braided channel sandstones are planar tabular lateral-connected sandbodies and the distribution of thick main channel belts can only be identified from 3-D seismic data.As the braided sandstones are ubiquitous,their occurrence and distribution do not need to be predicted.Generally,the coal velocity is so low that it can create a strong amplitude reflection in coal strata.It consequently conceals the amplitude respondence to anastomosing channel sandstone which could be identified from 3-D seismic inversion data sometimes.Case studies of mud-rich low-sinuosity rivers identified with 3-D seismic data indicate that the scales and width-to-thickness ratio of such sandbodies are small,laterally unconnected,and generally occurred on distant or further parts of an alluvial fan under dry climate conditions.Sometimes extraction of seismic attributes of every reflection event along horizons is expected to maximize expression of the spatial evolutions of ancient channels.